Safety Planning and Safety Control on Safety Performance - Ardhianto Gutomo Wisnupradhono; Muhammad Agung Wibowo; Budi Prasetyo Samadikun; Nurandani Hardyanti; Silviana; Sri Sumiyati (IJHCM (International Journal of Human Capital Management), 2023)
This study analyzes the influence of safety planning and safety control on safety performance. This study uses primary data from a survey using a questionnaire with a Likert scale of 1 to 5. This study uses 4,950 observational data with structural equation modeling analysis. This study uses safety planning and safety control as the independent variables and safety performance as the dependent variable. The results of this study indicate that safety planning has no significant effect on safety performance. Safety controls have a direct and significant effect on safety performance. This research is the first time in Indonesia to analyze the effect of safety planning and safety control on safety performance in building construction projects.